The Performance Testing Analysis Of Electric Wheelchair Batteries Under Various Operational Conditions - Rani Pratiwi; Solly Aryza; Amani Darma Tarigan (Jurnal Scientia, 2024)
An electric wheelchairs are vital mobility aids for individuals with mobility impairments or special needs. These wheelchairs rely on electric motors powered by batteries to provide the necessary propulsion. The accuracy and reliability of battery power measurement in electric wheelchairs are crucial for maintaining balance, stability, and ensuring a safe and comfortable user experience. One critical component in electric wheelchairs is the load cell, which measures the applied load such as user weight or additional loads. Over time, load cells may experience changes in their characteristics, such as sensitivity alterations or drift, potentially affecting load measurement accuracy. Therefore, calibration of load cell loads in electric wheelchairs becomes essential. Calibration ensures that load measurements remain accurate and consistent over time by comparing the output produced by the load cell with accurately known loads, and then adjusting the scale or resetting load cell parameters to achieve accurate measurements. This research aims to analyze the impact of load cell calibration on the performance of electric wheelchair batteries. The research questions include evaluating the effects of calibration on load measurement accuracy, identifying factors influencing load cell performance, and developing effective calibration methods. The study focuses on assessing how load cell calibration influences the performance of electric wheelchairs, with particular attention to measurement accuracy and stability aspects. The objective of this research is to enhance load measurement accuracy in electric wheelchairs through proper load cell calibration. The benefits include improving safety and comfort for wheelchair users by providing accurate load measurements, ensuring wheelchair balance and stability, and reducing the risk of injury or failure. Additionally, the findings contribute to the development of better electric wheelchair technology and enhance the quality of life for users.